Safe and effective re-use policy for high-efficiency filtering facepiece respirators (FFRS): Experience of one hospital during the Covid-19 pandemic in 2020 - Sergio I Prada; Álvaro Vivas; Maria Paula Garcia-Garcia; Erik Rosero; Marly Orrego; Juan Sebastián Candelo; John España; Germán Soto; Diego Martínez; Leonardo García (IPEM-Translation, 2022)
ABSTRACT: The high transmissibility rate of the Severe Acute Respiratory Syndrome Coronavirus 2 facilitated an exponential growth in the number of infections, posing a tremendous threat to healthcare systems across the world. The use of Non-oil 95% efficiency (N95) respirators demonstrated to reduce the risk of virus transmission. The escalated demand in N95 respirators during 2020 generated a massive shortage worldwide which resulted in serious implications, one being an increase in healthcare providers’ costs. In response, various optimization strategies were implemented. This study aimed to assess the implementation of a safe and effective re-use policy for high-efficiency filtering facepiece respirators (FFRs) in a high-complexity university hospital in 2020. Associated costs were estimated through a descriptive accounting analysis of resources saved. Acceptability, appropriateness, and feasibility rates were 80.5%, 78.8%, and 83.6%, respectively. With an implementation cost of approximately 10,000 USD, there was a 56.1% reduction in FFRs consumption, compared with a non-policy scenario, with savings exceeding 500,000 USD in 2020. In a pandemic scenario where it is vital to spare resources, a FFRs rational use policy demonstrated to be a highly cost-efficient alternative in order to save resources without increasing contagion risk among healthcare workers.